Zum Wanderungsverhalten der Westerner in der Republik Sudan - Beobachtungen im New Halfa- und im Rahad-Scheme - Heinritz, Günter (ERDKUNDE, 1981)
The migration flows induced by the development of the modern agrarian sector in the Sudan have their chief source areas in the western provinces of the Sudan and its neighbouring states to the west. The migrational behaviour of these immigrants is shown and analysed in the example of Westerners arriving at six camps of the New Haifa Schemeand the Rahad Scheme in February and November, 1979- In all the camps under investigation there was an amazingly high volume of migration with a high fluctuation, especially among one-person households. The places of origin of immigrants in the Rahad Scheme are less than 250 km away, and usually not identical with their place of birth, whereas the New Haifa Scheme, which has operated in Darfur and Kordofan for15 years, has already attained such a degree of renown that numerous Westerners move directly there. There is distinct evidence of chain effects in these moves, which must be attributed to the positive support for out-migration decision by the successful establishment of a relative in the target area. The existence of such a haven is of prime importance for the out-migrants, since they are usually too poor at the time of their departure to shoulder the risk of not imme diately finding employment in the target area.